Real Estate Taxes in Albania - Koprencka, Luciana; Cakrani, Edmira; Petani, Migena (European Journal of Sustainable Development, 2013)
The construction sector is one of the mainsectors of the Albanian economy, which,during the last 20 years, has experiencedthe greatest economic growth. In 1991 thissector has contributed by 2.5% to the GDP,in 2006 by 4.9%, while in 2008, this sectorhas contributed by 14.9% to the national GDP. The relevant legislation has played animportant role in the development of this sector. The applied laws have tried to maintainat low levels the real estate prices and totransform such a problematic sector, withreference to fiscal evasion and informality,into an easily controllable sector. The taxesapplied in the construction sector are the sameas in other economic sectors, although thetaxation management in the construction sector, except forthose common principles thatregulate the tax management in general, isbased on some specificrules related to thecharacteristics of this sector. Increase the level of taxation on the transfer of ownership tothe extent of 10%, paralyzed the housing market by reducing the number of sales,especially of real estate old, previously this was 0.3-5%of sales value.